Myocardial maladaptation to pressure overload in CB2 receptor-deficient mice - Duerr, Georg D.; Heinemann, Jan C.; Kley, Julian; Eichhorn, Lars; Frede, Stilla; Weisheit, Christina; Wehner, Sven; Bindila, Laura; Lutz, Beat; Zimmer, Andreas; Dewald, Oliver (Journal of molecular and cellular cardiology, 2019)
Background: Adaptation to aortic valve stenosis leads to myocardial hypertrophy, which has been associated with inflammation, fibrosis and activation of the endocannabinoid system. Since the endocannabinoid system and the CB2 receptor provide cardioprotection and modulate immune response in experimental ischemia, we investigated the role of CB2 in a mouse model of cardiac pressure overload. Methods: Transverse aortic constriction was performed in CB2 receptor-deficient (Cnr2−/−) mice and their wild-type littermates (Cnr2+/+). After echocardiography and Millar left heart catheter hemodynamic evaluation hearts were processed for histological, cellular and molecular analyses. Results: The endocannabinoid system showed significantly higher anandamide production and CB2 receptor expression in Cnr2+/+ mice. Histology showed non-confluent, interstitial fibrosis with rare small areas of cardiomyocyte loss in Cnr2+/+ mice. In contrast, extensive cardiomyocyte loss and confluent scar formation were found in Cnr2−/− mice accompanied by significantly increased apoptosis and left ventricular dysfunction when compared with Cnr2+/+ mice. The underlying cardiac maladaptation in Cnr2−/− mice was associated with significantly reduced expression of myosin heavy chain isoform beta and less production of heme oxygenase-1. Cnr2−/− hearts presented after 7 days with stronger proinflammatory response including significantly higher TNF-alpha expression and macrophage density, but lower density of CD4+ and B220+ cells. At the same time, we found increased apoptosis of macrophages and adaptive immune cells. Higher myofibroblast accumulation and imbalance in MMP/TIMP-regulation indicated adverse remodeling in Cnr2−/− mice. Conclusions: Our study provides mechanistic evidence for the role of the endocannabinoid system in myocardial adaptation to pressure overload in mice. The underlying mechanisms include production of anandamide, adaptation of contractile elements and antioxidative enzymes, and selective modulation of immune cells action and apoptosis in order to prevent the loss of cardiomyocytes.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Adaptive immune cells; Endocannabinoids; Myocardial hypertrophy; Remodeling